A f?bula como um elemento did?tico na forma??o leitora e na produ??o escrita de educandos do Ensino Fundamental: uma proposta de interven??o - Silva, Erika Romana Lacerda Barbosa da (2020)
This research develop a didactic intervention proposal, with the objective of increasing the quality of reading and writing of elementary school students, based on the concept of sociointeractionist teaching-learning. The discursive genre, chosen as a facilitating element for the execution of this work, was the fable, because it is narrative, concise, allegorical objective and brings, in itself, the very important moral element for the development of students' critical-reflective thinking, especially, for those who live in a region constantly affected by different types of violence. This paper, therefore, invests in a different didactic sequence aimed at elementary school students, especially for 7th grade students.